2018
DOI: 10.1097/qai.0000000000001781
|View full text |Cite
|
Sign up to set email alerts
|

Is on-Demand HIV Pre-exposure Prophylaxis a Suitable Tool for Men Who Have Sex With Men Who Practice Chemsex? Results From a Substudy of the ANRS-IPERGAY Trial

Abstract: Our findings show that chemsexers were more likely to report high-risk sexual practices but also had a higher perception of risk. They were also more likely to use PrEP correctly when practicing chemsex. Consequently, PrEP may be a suitable tool to reduce HIV-risk transmission among chemsexers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 41 publications
(44 reference statements)
5
28
2
1
Order By: Relevance
“…In PROUD, 44% (231/525) of participants reported using any of the three drugs most commonly associated with chemsex in the three months prior to enrolment [ 12 ]. In the IPERGAY study in France, 29% (95/331) of participants reported chemsex and interestingly chemsex users were twice as likely to use PrEP the last time they had sex than non-users [ 25 ]. Evidence from both trials, and from a recent evaluation of PrEP use among chemsex users in Australia, suggests that MSM engaging in chemsex are incorporating PrEP into their sexual practice [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In PROUD, 44% (231/525) of participants reported using any of the three drugs most commonly associated with chemsex in the three months prior to enrolment [ 12 ]. In the IPERGAY study in France, 29% (95/331) of participants reported chemsex and interestingly chemsex users were twice as likely to use PrEP the last time they had sex than non-users [ 25 ]. Evidence from both trials, and from a recent evaluation of PrEP use among chemsex users in Australia, suggests that MSM engaging in chemsex are incorporating PrEP into their sexual practice [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the same research also suggested that on average “club drug” users were no more likely to miss PrEP doses than non “club drugs” users (Grov, Rendina, John, & Parsons, 2018), and in another study among American GBM, methamphetamine use was shown not to be associated with decreased PrEP adherence (Hoenigl et al., 2019, Hoenigl et al, 2019). Interestingly, in an IPERGAY trial substudy, GBM reporting chemsex were more likely to report correct PrEP use during their most recent sexual encounter, which authors have explained by their additional finding that participants reporting chemsex also reported having a higher risk perception (Roux et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, a study based in France on episodic PrEP use highlighted that 30% of the sample had been under the influence of psychoactive substances during sex. 9 This study also reported that the correct use of PrEP was associated with periods when sample members were under the influence of psychoactive drugs during sex. 9 PrEP's effectiveness is dependent on medication adherence, but this study could not examine this area as these data were not collated.…”
Section: Discussionmentioning
confidence: 72%
“… 9 This study also reported that the correct use of PrEP was associated with periods when sample members were under the influence of psychoactive drugs during sex. 9 …”
Section: Discussionmentioning
confidence: 72%